Standard operating procedures for biobank in oncology - Bonizzi, Giuseppina; Zattoni, Lorenzo; Capra, Maria; Cassi, Cristina; Taliento, Giulio; Ivanova, Mariia; Guerini-Rocco, Elena; Fumagalli, Marzia; Monturano, Massimo; Albini, Adriana; Viale, Giuseppe; Orecchia, Roberto; et al. (Frontiers in Molecular Biosciences, 2022)
Biobanks are biorepositories that collect, process, store, catalog, and distribute human biological samples, and record the associated data. The role and action field of these strategic infrastructures for implementing precision medicine in translational research is continuously evolving. To ensure the optimal quality at all stages of biobanking, specific protocols are required and should be elaborated following existing guidelines, recommendations, laws, and rules. This article illustrates the standard operating procedures, including protocols, troubleshooting, and quality controls, of a fully certified biobank in a referral Cancer Center. This model involves all clinical departments and research groups to support the dual mission of academic cancer centers, i.e. to provide high-quality care and high-quality research. All biobanking activities according to different types of biological specimens are detailed and the most tricky methodological aspects are discussed, from patients' informed consent to specimen management.